A FRAMEWORK FOR IMAGE SYNCHRONIZATION BETWEEN MOBILE NOSQL DATABASE AND SERVER-SIDE SQL DATABASE IN HETEROGENEOUS DATABASES - ZULKAFLI, ABU ZARIN (2018)
The emergence of media entertainment had introduced unstructured multimedia data like images that require big memory allocation for data storage and need efficient method to synchronize activities. Some software and mobile application developers tend to implement schema-less databases, known as NoSQL